1997
DOI: 10.1038/bjc.1997.510
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anti-tumour lymphocytes in cancer patients after brief exposure to supernatants from cultures of anti-CD3-stimulated allogeneic lymphocytes

Abstract: Summary The present study investigated the ability of supernatants collected from cultures of healthy donor-derived peripheral blood mononuclear cells (HD-PBMCs) stimulated with anti-CD3 monoclonal antibody (MAb) (allogeneic CD3 supernatants; ACD3S) to induce, upon brief exposure, tumour-reactive cytotoxic lymphocytes in cancer patients' PBMCs. ACD3S enhanced natural killer (NK) and lymphokineactivated killer (LAK) cell-mediated cytotoxicity. ACD3S contained increased levels of interleukins (IL) 1, 2, 6, 7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Previous reports by our group [26,33], have demonstrated reduced levels of these monokines in patients with various types of cancer and deficiencies in functional activities of antigen presenting cells in cancer patients have also been reported by others. In particular Ninomiya et al [34] have demonstrated that monocytes from patients with hepatocellular carcinoma expressed low levels of HLA-DR, induced decreased amounts of IL-12 and were less potent in stimulating MLR responses.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous reports by our group [26,33], have demonstrated reduced levels of these monokines in patients with various types of cancer and deficiencies in functional activities of antigen presenting cells in cancer patients have also been reported by others. In particular Ninomiya et al [34] have demonstrated that monocytes from patients with hepatocellular carcinoma expressed low levels of HLA-DR, induced decreased amounts of IL-12 and were less potent in stimulating MLR responses.…”
Section: Discussionsupporting
confidence: 51%
“…PBMCs stimulation with anti-CD3 mAb was performed as recently reported [24,26]. In brief, PBMCs (2×10 6 cells/ml) were activated in 25-cm 2 flasks (Costar), precoated with anti-CD3 mAb in 5 ml of culture medium.…”
Section: Stimulation With Anti-cd3 Mabmentioning
confidence: 99%
“…Unlike CTL, NK cells kill their targets spontaneously and without restriction by MHC. On the other hand, LAK cells generated in cultures with IL-2, which can be of T or NK cell origin [12,13], lyse tumor cells including those that are NK resistant, in a non-MHC-restricted fashion [13]. The mechanisms of cytotoxicity utilized by all three types of effectors mentioned are classified into secretory and nonsecretory pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, deficiencies in functional activities of antigen-presenting cells in cancer patients have also been previously reported [14,31]. Monocytes from patients with hepatocellular carcinoma express low levels of HLA-DR, decreased amounts of IL-12 and were less potent in stimulating auto-MLR responses [32].…”
Section: Discussionmentioning
confidence: 99%
“…This was performed as recently reported [12,14]. In brief, PBMCs (2 × 10 6 cells/ml) were activated in 25 cm 2 flasks (Costar), precoated with anti-CD3 mAb in 5 ml of culture medium.…”
Section: Methodsmentioning
confidence: 99%